2012
DOI: 10.1111/j.1445-2197.2012.06034.x
|View full text |Cite
|
Sign up to set email alerts
|

Open rotator cuff repairs in patients 70 years and older

Abstract: Level IV (observational study without control - retrospective study).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Amid all confusion and controversies, there are surgeons who recommended repair for all symptomatic individuals, regardless of age [6] . However, there is a genuine paucity of literature recommending rotator cuff repair in patients aged 70 years and older [17,18] and only a few studies have published all arthroscopic rotator cuff repair (ARCR) in this particular age group [15,19] .…”
Section: Clinical Outcome Of Arthroscopic Rotator Cuff Repair In Patimentioning
confidence: 99%
“…Amid all confusion and controversies, there are surgeons who recommended repair for all symptomatic individuals, regardless of age [6] . However, there is a genuine paucity of literature recommending rotator cuff repair in patients aged 70 years and older [17,18] and only a few studies have published all arthroscopic rotator cuff repair (ARCR) in this particular age group [15,19] .…”
Section: Clinical Outcome Of Arthroscopic Rotator Cuff Repair In Patimentioning
confidence: 99%
“…Currently, over 300,000 surgeries are performed annually in the United States to repair rotator cuff tears [3], and this number is likely to rise with the projected increase in elderly populations [4]. Re-tear rates are high, especially with increasing tear size [5,6], and massive rotator cuff tears may not be amenable to traditional suture repair [7].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been recently published on rotator cuff repair in patients over 60 and 70 years of age. De Carvalho et al 45 reviewed 104 cases of openly repaired RCTs in a group of patients with a mean age of 77 years and reported a high satisfaction rate of 92.7%, as well as pain relief and high-level function. However, a recent systematic review concluded that, although there could be a benefit of a surgical approach, the heterogeneity of the treatments does not allow generalization.…”
Section: Degenerative Pathologymentioning
confidence: 99%